High solid content production of environmentally benign ultra-thin lignin-based polyurethane films: Plasticization and degradation. (12th September 2019) - Zhang, Yan; Wang, Jingya; Fang, Xiangchen; Liao, Jianjun; Zhou, Xin; Zhou, Shumin; Bai, Fudong; Peng, Shaozhong
Abstract: Here, an environmentally benign method of minimizing waste creation and production time was proposed to fabricate the ultra-thin polyurethane films (LPUf s). The lignin was used as hard segments and poly(ε-caprolactone) glycol (PCL) served as soft segments through the coupling of hexamethylene diisocyanate (HDI). The modified fabrication method could economize the usage of solvent more than six-fold and reduce the production time within 6 h. Several types of additives such as epoxidized soybean oil (ESO), dioctyl sebacate (DOS), acetyl tributyl citrate (ATBC), cardanol and antisticking agent were incorporated to improve the performance of the films and the ATBC has advantages as plasticizer for the LPUf . The biofilm was flexible and foldable without breaking at the thickness of 20 μm, the optimized elongation at break and tensile strength could reach 246.36% and 16.68 MPa, respectively. Moreover, the bio-polyurethane revealed outstanding UV-shielding capacity and excellent biodegradability in the soil due to the green lignin and PCL. Thus this strategy enabled the high efficient production of sustainable polyurethane from renewable and nontoxic lignin using less organic solvents. Graphical abstract: The flexible and foldable ultra-thin polyurethane film was fabricated by a high solid content method with reducing the usage of solvent more than six-fold and production time within 6 h. This strategy enabled the high efficient production of biodegradable and sustainable polyurethane films from renewable and nontoxic lignin.Image 1 Highlights: Ultrathin biodegradable polyurethane films have been successfully prepared using a very simple and high-efficient reaction. The usage of solvent was economized more than six-fold and the production time decreased within 6 h. The additives were incorporated to improve the comprehensive performance of the films. Incorporation of green lignin and PCL endowed polyurethane remarkable biodegradability.